Illness concepts among patients with benign and malignant mammary tumors - Lali M. Kogoniya; Anna S. Nelubina; Ekaterina V. Markarova; Ekaterina E. Tuntsova (LLC "MEDIAFORMAT", 2020)
The paper reports variants of subjective illness perception in patients with benign and malignant mammary tumors. The study included 100 patients followed-up in the Vladimirsky Moscow Regional Research Cinical Institute (MONIKI) (50 patients with stage II-III breast cancer and 50 patients with fibrocystic breast changes). The study provided data on subjective illness concept variants for patients of both groups which defined the illness behavior of patients, including the non-compliant behavior. The results obtained may be used for development of disease prevention programs (primary and secondary prevention).